INTERWEAVING CHARACTER EDUCATION IN ENGLISH TEXTBOOK OF SENIOR HIGH SCHOOL - Saadillah Saadillah; Afifah Linda Sari; Annisa Khairir Rizki (LET: Linguistics, Literature and English Teaching Journal, 2020)
This research is aimed at find out the character education values in reading materials of English textbook which is published by Yudhistira and Tiga Serangkai. This research used the textbook that is used by the eleventh grade of Senior High School as a handbook. This study is a descriptive qualitative research by doing content analysis. In conducting the research, the researchers analyzed the reading materials provided in the textbook by analyzing the material and determined the genre and character education value of the text. Throughout the analysis, the researchers found 15 character education values are inserted in reading text material, involve: Friendly, Social Care, Love Peace, Curiosity, Religious, Joy of Reading, Tolerance, The Spirit of Nationality, Love Homeland, Creative, Discipline, Rewarding Achievement, Hard Work, Environmental Care, and Responsibility. The teachers assess the character education values directly and joined with other evaluation, in the form of Affective. Therefore, the finding of this research is expected for the teacher to come up with the moral education which inserted in reading materials. Furthermore, in the future character education is intended can be developed and fully realized in the school practices.